2015
DOI: 10.1021/acs.nanolett.5b02683
|View full text |Cite
|
Sign up to set email alerts
|

Unified Description of the Optical Phonon Modes in N-Layer MoTe2

Abstract: N -layer transition metal dichalcogenides provide a unique platform to investigate the evolution of the physical properties between the bulk (three dimensional) and monolayer (quasi two-dimensional) limits. Here, using high-resolution micro-Raman spectroscopy, we report a unified experimental description of the Γ-point optical phonons in N -layer 2H-molybdenum ditelluride (MoTe2). We observe a series of N -dependent low-frequency interlayer shear and breathing modes (below 40 cm −1 , denoted LSM and LBM) and w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
245
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(285 citation statements)
references
References 53 publications
39
245
1
Order By: Relevance
“…3c). Indeed, as already reported 22 , this peak has an energy that depends on the number of layers, appears in the Raman scattering spectrum as a single component feature for 1L-MoSe 2 and 2L-MoSe 2 , splits into two components for 3L-MoSe 2 and 4L-MoSe 2 and into three 20,29,43 , can be used to determine the number of layers. Close to 252 cm −1 , another Raman scattering feature is observed with an energy that changes with the number of layer.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…3c). Indeed, as already reported 22 , this peak has an energy that depends on the number of layers, appears in the Raman scattering spectrum as a single component feature for 1L-MoSe 2 and 2L-MoSe 2 , splits into two components for 3L-MoSe 2 and 4L-MoSe 2 and into three 20,29,43 , can be used to determine the number of layers. Close to 252 cm −1 , another Raman scattering feature is observed with an energy that changes with the number of layer.…”
supporting
confidence: 57%
“…Similar to the TO E'/E g at 289 cm −1 and to the A" 2 /A 1g mode at 354 cm −1 , the breathing mode's intensity seems to show a resonance with electronic excitations above the energy of the C exciton. For different MX 2 materials, depending on the excitation laser and on the exciton energy structure, very different intensity ratios between the shear and breath modes have been reported recently 19,29,34,35,44 . As follows from the study reported here, these differences arise from the peculiar resonance effect affecting differently the two modes.…”
Section: Nmmentioning
confidence: 98%
“…[1,8] They have attracted extensive research attention in recent years due to their appeals in microelectronic, optoelectronic, spin and valley electronic applications. [1,9,10,11,12] The 1T' or Td phase MX 2 are of the distorted 1T structure, which usually show semi-metallic behavior. [3,[13][14][15] Examples of the latter include WTe 2 and -MoTe 2 , which have drawn special interests lately following some recent revelations of, e.g., the large and unsaturated magnetoresistance, [4,15,16,17,18] pressure-driven superconductivity, [7,19] novel optical properties and characteristics, [11,12,17,18,20] and the topological insulator [14] and Weyl semimetal states.…”
mentioning
confidence: 99%
“…Here, we investigate its effect on Raman scattering. Raman spectroscopy has been used extensively on 2D materials, such as graphene and TMDC's, for studying thicknessdependent properties [13][14][15][16][17][18][19][20] and probing strain effects [21,22]. However, few Raman studies have examined systematically the polarization selection rule for TMDCs with circularly polarized excitation and detection [23].…”
mentioning
confidence: 99%